Effectiveness of Metoprolol in Improving Cardiac and Motor Functions in Patients with Chronic Heart Failure: A Prospective Study - Cheng X; Zhu M; Liu Q; Feng Z; Meng Y (Dove Medical Press, 2020)
XiaoLiang Cheng,1 Min Zhu,2 Qing Liu,3 Zhenxia Feng,2 Yong Meng2 1Department of Endocrinology, The Second Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, People’s Republic of China; 2Department of Cardiology, The Second Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, People’s Republic of China; 3School of Public Health, Kunming Medical University, Kunming, Yunnan, People’s Republic of ChinaCorrespondence: Yong Meng Email mengyong@kmmu.edu.cnPurpose: To assess gender-, age-, and the dose-related influence of metoprolol on cardiac function, motor function, quality-of-life (QoL), and mental status in Chinese chronic heart failure (CHF) patients.Patients and Methods: This single-center, prospective study enrolled CHF patients with resting heart rate (HR) > 80 bpm and used metoprolol continuous release tablets. Patients were initiated with 12.5-mg metoprolol. All patients were assessed for change in cardiac function, motor function, QoL, and mental status according to gender (men vs women), age (< 60 vs ≥ 60 years), and metoprolol dose administered (47.5 mg [n=37], 71.25 mg [n=7], 118.75 [n=74], and 142.5 mg [n=19]).Results: Overall, 154 CHF patients (101 men and 53 women), with median age 66.39 years, were enrolled. In total, 116 and 38 patients were aged ≥ 60 and < 60 years, respectively. We observed a slight decrease in systolic blood pressure (SBP) in women compared with men. HR had increased with an increase in ejection fraction (EF) from baseline to 1 month (35.24± 6.15 and 34.79± 6.25) and increased to 50.00± 4.45 and 50.72± 4.09 among both the genders. Cardiac index (CI) and motor function had improved along with better QoL after metoprolol treatment in both the genders. In both age groups (< 60 and ≥ 60 years), improvement in cardiac function, motor function, and QoL was observed; however, there was a difference in mental status. The dose effect of metoprolol on cardiac function, motor function, QoL, and mental status showed a gradual decrease in EF with dose increments, with no change in CI. Motor function, QoL, and mental status did not show much difference with uptitration of metoprolol dose.Conclusion: Psychological responses to metoprolol treatment differ with gender, with no age-related changes in terms of cardiac function, motor function, QoL, or mental status, except increases in depression, burnout, and anxiety.Keywords: metoprolol, chronic heart failure, quality-of-life, heart rate, psychological responses